Chinese folklore studies today : discourse and practice (Indiana University Press, 2019)
Chinese folklorists are well acquainted with the work of their English-language colleagues, but until recently the same could not be said about American scholars' knowledge of Chinese folkloristics. Chinese Folklore Studies Today aims to address this knowledge gap by illustrating the dynamics of contemporary folklore studies in China as seen through the eyes of the up-and-coming generation of scholars.